2018
DOI: 10.1161/circulationaha.118.033939
|View full text |Cite
|
Sign up to set email alerts
|

TBX20 Regulates Angiogenesis Through the Prokineticin 2–Prokineticin Receptor 1 Pathway

Abstract: Our study identifies TBX20 as a novel transcription factor regulating angiogenesis through the PROK2-PROKR1 (prokineticin receptor 1) pathway in both development and disease and reveals a novel mode of angiogenic regulation whereby the TBX20-PROK2-PROKR1 signaling cascade may act as a "biological capacitor" to relay and sustain the proangiogenic effect of vascular endothelial growth factor. This pathway may be a therapeutic target in the treatment of diseases with dysregulated angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“… 119 121 Besides, Tbx20 participated in the signaling cascade of Tbx20-PROK2-PROKR1 and regulated angiogenesis. 122 The above findings provide further mechanistic insights into the link between cardiomyocyte proliferation and cardiac regeneration.…”
Section: Proliferation and Mitosis Of Pre-existing Cardiomyocytesmentioning
confidence: 78%
“… 119 121 Besides, Tbx20 participated in the signaling cascade of Tbx20-PROK2-PROKR1 and regulated angiogenesis. 122 The above findings provide further mechanistic insights into the link between cardiomyocyte proliferation and cardiac regeneration.…”
Section: Proliferation and Mitosis Of Pre-existing Cardiomyocytesmentioning
confidence: 78%
“…PROK2, also named Bv8, is a ligand for a G protein-coupled receptor, PROKR2. Recently, it has been found that the PROK2-PROKR2 pathway is crucial for angiogenesis in embryonic development and that the expression of PROK2 is regulated by the TBX20 transcription factor 51 . Considering that the products of genes causative of KS contribute to embryonic angiogenesis, abnormality in the angiogenic process appears to be important for the pathogenesis of KS.…”
Section: Discussionmentioning
confidence: 99%
“…In the recently published study by Meng et al, the authors sought to analyse the function of the key transcription factor T-box 20 (TBX20) and the signaling pathway which is activated during angiogenesis (7). TBX20 is considered a pivotal transcription factor during embryogenesis.…”
Section: The Study By Meng Et Almentioning
confidence: 99%
“…PROK2 that acts on its receptor PROKR1in an autocrine fashion. The authors presume that this mechanism might help to further sustain the pro-angiogenic signalling [adapted fromMeng et al(7)].…”
mentioning
confidence: 99%